Homophobic bullying research and theoretical perspectives - Rivers, Ian. (New York ; Oxford : Oxford University Press, 2011)
Using theories and ideas drawn from various disciplines, the author demonstrates how bullying is a complex social process wherein perpetrators are supported by active confederates, passive bystanders and indifferent onlookers.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Homophobia in schools -- Great Britain; Bullying in schools -- Great Britain